The links between climate change, disasters, migration, and social resilience in Asia a literature review. - Ober, Kayly; Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
Disasters are increasingly causing mass movements of people all over the world, but especially in Asia. While sheer numbers are important, they tell us little about how disasters impact the movement of people in Asia and to what extent people ability to overcome poverty and build their resilience are affected. In what ways do disasters determine where, when, and how people move? How do disasters affect this movement across differentiated segments of society, including socioeconomic status, gender, and age? In what ways does migration affect vulnerability and resilience in the face of disaster?
Keywords: Climatic change; Natural disasters -- Risk assessment -- Asia; Natural disasters -- Economic aspects; Electronic book